Characterization of arterial stiffness in cancer patients: making the case for clinical implementation - Parr, Shannon Kay (Kansas State University, 2023)
Monitoring changes in left ventricular function is the primary surveillance strategy in cardio-oncology practice for detecting cardiotoxicity in cancer patients actively receiving treatment and in the survivorship phase. The current clinical manifestation of cardiotoxicity is defined by reductions in left ventricular ejection fraction and global longitudinal strain, primarily reflections of cardiac systolic function. Recent evidence, however, has suggested that vascular function is reduced following anti-cancer chemotherapy. These vascular abnormalities manifest as reduced endothelial function, increased vascular smooth muscle tone, and arterial stiffness, and often occur in the absence of clinically significant changes in cardiac function. Of these, increased arterial stiffness has been linked to adverse cardiac outcomes including heart failure and cardiac remodeling, in the general and various clinical populations; but it has yet to be incorporated into regular clinical practice due to methodological challenges. Therefore, the primary aim of this dissertation was to fully characterize the association of arterial stiffness and cancer and develop a clinically feasible method to measure arterial stiffness into practice. The first investigation of this dissertation (Chapter 2) demonstrates arterial stiffness increases in a diverse group of cancer patients after exposure to heterogenous therapy regimens. Our second investigation from Chapter 3 demonstrates that pulse pressure, an index of arterial stiffness, is predictive of all-cause mortality and cardiovascular mortality in a retrospective data set of participants with a history of cancer. From this work that established that arterial stiffness increases with cancer treatment and is predictive of long-term outcomes in cancer populations, we developed a clinically relevant method to measure arterial stiffness in the clinic for Chapter 4. Specifically, this method is focused on the evaluation of aortic arch stiffness leveraging the standard scanning views obtained during routine transthoracic echocardiography. Taken together, our data suggests arterial stiffness increases following anti-cancer chemotherapy and predicts long-term adverse outcomes. This work begins to make a compelling case for monitoring stiffness in the clinic, and our newly proposed method represents an avenue to incorporate vascular measures into cardio-oncology risk stratification.
Keywords: Cardio-oncology; Arterial stiffness; Vascular dysfunction; Cardiotoxicity; Chemotherapy; Pulse pressure